ANALISIS KONDISI LALU LINTAS JALAN MAYJEND SUTOYO CAWANG - Efendy Tambunan (UKI Press, 2022)
The Cawang transmission lines are both a strategic location and a gateway for traffic moving from Bogor, Depok, and Bekasi to Jakarta, and thus a center point or integration point for modes such as TransJakarta buses, commuter trains, the Halim Perdana Kusuma Airport, LRT from Cimanggis and East Bekasi, and high-speed trains from Bandung to Jakarta. Jakarta's traffic has been becoming increasing after declining the post-Covid-19 pandemic. A study was conducted on Mayjen Sutoyo Street, which stretches about two kilometers from MT Haryono Road and DI Pandjaitan Road to the intersection of Jalan Dewi Sartika and Jalan Cililitan Besar, to determine the performance of the traffic in the Jakarta area. In addition to its strategic location, the location selected for this study results in traffic congestion on this road, especially during peak traffic. This research aims to determine the road section's traffic flow, speed, density, and service level. The traffic survey records vehicle data from the Jayakarta Regional Military Command Building to the UKI Cawang traffic light. MKJI 1997 was applied to data processing. According to data research, the service level index for Mayjen Sutoyo Road Cawang belongs to category E